The Power Relationship of Alumni in Maintaining The Seniority Culture At SMAN “X” Surabaya: A Case Study on the Culture of Violence in Schools - Aditia, Rifqi Dwinanda Aditia (Paradigma, 2026)
This study discusses the power relations of alumni in maintaining the culture of seniority at State Senior High School “X” in Surabaya. The main focus of this study is how alumni play an important role in establishing and perpetuating traditions as a distinctive identity of the school. These traditions are rooted in the values of togetherness, solidarity, and loyalty, which then develop into a hierarchical system between alumni and active students. Schools, as educational institutions that should be places where students can develop their academic potential, have instead become arenas for seniority, which is very detrimental. Although seniority is not visible to the public, it can be felt directly by those concerned, such as the students at these schools. This is especially true at State Senior High School “X” in Surabaya, which has a culture of seniority among its students that has long been a tradition passed down from generation to generation. The culture of seniority in schools does not arise spontaneously, but is formed through discursive practices that continue to be reproduced across generations through S-mania. These practices contain elements of power that have the potential for violence, which is legitimized as a form of discipline and loyalty to the school. Even though they no longer have a formal relationship with the school institution, alumni still play an important symbolic and normative role in maintaining the values and traditions of S-mania. This process creates a hierarchical structure between alumni, senior students, and new students that places power in a vertical pattern. The culture of seniority that occurs at SMA Negeri “X” Surabaya has a negative influence. The concept of seniority has its own mechanism whereby the upper echelons dominate the social structure to enforce and have rules implemented through S-mania. These rules are more inclined to discipline younger students and force them to submit to their seniors through S-mania.